2020
DOI: 10.1021/acs.jpcc.0c00883
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of Dehydrogenated Polycyclic Aromatic Hydrocarbons on Highly Oriented Pyrolytic Graphite

Abstract: Electron impact ionization was used to generate dehydrogenated monocationic fragments of polycyclic aromatic hydrocarbons (PAHs) coronene, pentacene, hexabenzocoronene, dicoronylene, and rubrene. Upon mass-selective soft-landing deposition onto highly oriented pyrolytic graphite (HOPG) surfaces, these dehydrogenated monomeric species can form strongly bound dimers and oligomers interlinked via newly formed annulated benzene rings as detected by subsequent desorption experiments. The oligomerization degree can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Initial structures are generated by placing two separate monomers randomly on the surface of graphene. The number of hydrogen vacancies were initially set to 2 and 4 for the coronene monomer and the pentacene monomer to be consistent with the chemical formulas of the coronene dimer ([Cor−2H] 2 ) and the pentacene dimer ([Pen−4H] 2 ) in Weippert et al 14 . During the search of the pentacene dimer, we found the configuration in with 5 C-C bonds connect two monomers had much lower energies than the one with 4 connecting C-C bonds.…”
Section: B Structure Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial structures are generated by placing two separate monomers randomly on the surface of graphene. The number of hydrogen vacancies were initially set to 2 and 4 for the coronene monomer and the pentacene monomer to be consistent with the chemical formulas of the coronene dimer ([Cor−2H] 2 ) and the pentacene dimer ([Pen−4H] 2 ) in Weippert et al 14 . During the search of the pentacene dimer, we found the configuration in with 5 C-C bonds connect two monomers had much lower energies than the one with 4 connecting C-C bonds.…”
Section: B Structure Searchmentioning
confidence: 99%
“…self-assembly of PAH on graphite 13 ) is an important ingredient in soot particle and dust grain chemistry as well. Recently, the chemical dimerization of dehydrogenated PAHs on graphite has been studied using laser desorption coupled with ion mobility spectrometry 14 . In this work, some possible dimer structures are proposed by gas phase density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “bottom-up” formation of large PAHs/quantum dots and C 60 from smaller molecular precursors has received increasing attention recently from both terrestrial and astronomical perspectives through both gas and surface reactions. For generation of large PAHs on non-metallic surfaces, approaches include thermal fusion of coronene ( Talyzin et al, 2011 ) and pentacene ( Ishii et al, 2011 ), soft X-ray irradiation of pentacene ( Heya et al, 2020 ), and oligomerization of dehydrogenated PAHs deposited as cations from the gas phase ( Weippert et al, 2020 ). In respect of fullerene formation, this route is supported by experimental observation of C 60 formation during the pyrolysis of PAHs ( Taylor et al, 1993 ; Osterodt et al, 1996 ), laser pyrolysis of hydrocarbons ( Ehbrecht et al, 1993 ; Armand et al, 1997 ) and laser desorption ionisation (LDI) of triphenylene in an experiment that combines LDI with ion-mobility mass spectrometry ( Han et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…17−19 It has been shown that the chemistry and reactivity of PAHs are of valuable interest for the synthesis of graphene sheets of nanoribbons, which is of particular concern for nanoelectronics and spintronics. 20,21 Finally, PAHs, and more particularly PAHs adsorbed on relatively inert substrates, constitute template molecules or systems for the development of theoretical calculations and more especially in the framework of van der Waals density functional theory (DFT). 22−25 From the above reasons, it appears clearly that understanding the reactivity of PAHs and their derivatives, as well as their on-surface behavior, is of particular importance due to their potential implications in astrochemistry, nanoelectronics, and fundamental sciences.…”
Section: ■ Introductionmentioning
confidence: 99%